I am pretty new to calculus and would like a nudge in the right direction in order to complete this question properly (Maybe also correct any misrepresentations I have about integration)

So the question is this:


My attempt at a solution:

let $$u=\sqrt{x}$$ $$u^2={x}$$

thus $$\frac{du}{dx}=\frac{1}{2}x^{-1/2}$$ $$dx=x^{1/2}2du=2udu$$

Now, $$\int_{a}^{b}u^{2}\sqrt{1-u}\:2udu\:$$



I am able to substitute $\sqrt{x}$ for u, and solve the integral, but i don't believe this gives me the correct solution.

Can anyone point me towards a mistake, mis-conceptualization or different substitution that would allow me to solve this question?

The question is tagged as dual substitution, does that mean i need to substitute two factors, or that multiple substitutions will work for this integral?


P.S. Feel free to clean up my LaTex

  • 2
    $\begingroup$ Where did that last line "$=2(\frac{1}{3}u^{3}*\frac{2}{3}({1-u})^{3/2}*\frac{1}{2}u^{2}*\frac{1}{2}u^{2})$" come from? $\endgroup$ – user137731 Jan 12 '16 at 19:04
  • $\begingroup$ The method looks OK to me, for the last step you are going to have to integrate by parts. I am not sure the final answer given there is correct. Also, why have you left your bounds near the end as $a,b$? The substitution $u = 1-\sqrt{x}$ also works. $\endgroup$ – fosho Jan 12 '16 at 19:06
  • $\begingroup$ Bye_world: I am not sure if i integrated properly considering i used the chain rule to integrate $(1-u)^{1/2}$ $\endgroup$ – helpmeh Jan 12 '16 at 19:09
  • $\begingroup$ Workaholic, ill try that and post my attempt $\endgroup$ – helpmeh Jan 12 '16 at 19:10
  • 1
    $\begingroup$ @helpmeh The chain rule states that $f(g(x))'=f'(g(x))\cdot g'(x)$, how did you use it to find the antiderivative? $\endgroup$ – Workaholic Jan 12 '16 at 19:11

In my previous answer I ended where I assumed you could take over. I guess that was a false assumption. In this answer I'll try to explain each step.

Start with the integral $$\int_{x=0}^{x=1} x\sqrt{1-\sqrt{x}}\ dx$$

Here I'd be a bit more ambitious than you. I know that anything other than simply a variable under a square root is going to cause me trouble so I'm going to try to substitute everything under the outer square root.

Let $u = 1-\sqrt{x}$. This implies that $$du = \frac{d(1-\sqrt{x})}{dx}\ dx = -\frac{1}{2\sqrt{x}}\ dx = -\frac 1{2(1-u)}\ dx \\ \implies -2(1-u)\ du = dx$$

We also will need to substitute for $x$ so notice that $u=1-\sqrt{x} \implies x=(1-u)^2$.

Now we make this substitution. Notice how I evaluate the bounds:

$$\begin{align}\int_{x=0}^{x=1} (1-u)^2\sqrt{u}\big(-2(1-u)\ du\big) &= -2\int_{u=1-\sqrt{0}}^{u=1-\sqrt{1}} (1-u)^3\sqrt{u}\ du \\ &= -2\int_{u=1}^{u=0} (1-u)^3u^{1/2}\ du \\ &= 2\int_{u=0}^{u=1} (1-u)^3u^{1/2}\ du\end{align}$$

From here we should just simplify $(1-u)^3u^{1/2}$. $$(1-u)^3u^{1/2} = (1-3u+3u^2-u^3)u^{1/2} = u^{1/2}-3u^{3/2}+3u^{5/2}-u^{7/2}$$

Now we can use this and the fact that $\int_a^b (\beta f(x) + \gamma g(x))\ dx = \beta\int_a^b f(x)\ dx + \gamma\int_a^b g(x)\ dx$ to get our integral into a form we know how to evaluate.

$$\begin{align}2\int_{u=0}^{u=1} (1-u)^3u^{1/2}\ du &= 2\int_0^1 (u^{1/2}-3u^{3/2}+3u^{5/2}-u^{7/2})\ du \\ &= 2\left(\int_0^1 u^{1/2}\ du -3\int_0^1 u^{3/2}\ du + 3\int_0^1 u^{5/2}\ du -\int_0^1 u^{7/2}\ du\right) \\ &= 2\int_0^1 u^{1/2}\ du -6\int_0^1 u^{3/2}\ du + 6\int_0^1 u^{5/2}\ du - 2\int_0^1 u^{7/2}\ du\end{align}$$

At this point we remember that the antiderivative of $x^k$ is $\frac 1{k+1}x^{k+1}$ and get the answer:

$$2\int_0^1 u^{1/2}\ du -6\int_0^1 u^{3/2}\ du + 6\int_0^1 u^{5/2}\ du - 2\int_0^1 u^{7/2}\ du\ = \left.\big(2\frac 23u^{3/2} -6\frac25u^{5/2} +6\frac27u^{7/2}-2\frac29u^{9/2}\big)\right|_{\ 0}^{\ 1} \\ = \frac 43-\frac{12}5+\frac{12}7-\frac 49$$

  • 1
    $\begingroup$ thanks for your help you are a good person :) $\endgroup$ – helpmeh Jan 12 '16 at 21:16

At the line $$=2\int_{0}^{1}u^{2}\sqrt{1-u}\:udu = 2\int_0^1 u^3\sqrt{1-u}\ du$$

(why did I set the bounds $=0$ and $1$?) you could do integration by parts, but since you say you're a "beginner", why not just use another substitution: Let $w=1-u$, then $dw=-du$.

$$=-2\int_1^0 (1-w)^3\sqrt{w}\ dw = 2\int_0^1 (1-w)^3\sqrt{w}\ dw$$ Then if you expand this out (meaning $(1-w)^3\sqrt{w} = (1 -3w + \cdots)\sqrt{w} = w^{1/2}-3w^{3/2}+\cdots$) you'll just be left with several integrals of the type $\int aw^k\ dw$ which hopefully you know how to evaluate. Good luck. :)

  • $\begingroup$ this is helpful, AFAIK the bounds do not need to be set until I am ready to solve the integer. However i have never seen the notation dw, I am assuming it is simply a second substitution, I am going to have some food and come back to this question with a vengeance $\endgroup$ – helpmeh Jan 12 '16 at 19:15
  • $\begingroup$ The bounds I obtained by simply setting $x=0$ and $1$ in the change-of-variables equation $u=\sqrt{x}$. Later I found the bounds in the integration wrt $w$ by setting $u=0$ and $1$ in the change-of-variables equation $w=1-u$. As for what $dw$ is -- it's the same thing as $du$ and $dx$, I just had to choose a new name for the variable of integration because $x$ and $u$ were already taken. $\endgroup$ – user137731 Jan 12 '16 at 19:19

attempt numero dos, (thanks to @bye_world) (third time maybe charm)

from $$=2\int_{a}^{b}u^{2}\sqrt{1-u}\:udu$$


let $$w=1-u\:$$ $$u=1-w\:$$ and $$\frac{dw}{du}=-1$$ $${-dw}={du}$$

so, $$=2\int_{b}^{a}({1-w})^{3}\sqrt{w}\:dw$$ $$=2\int_{b}^{a}(-w^{7/2}+3w^{5/2}-3w^{3/2}+w^{1/2})\:dw$$

Okay, I think I get what you guys are trying very hard to get through to me, $\int{f(x)+g(x)+h(x)}$ can be split up into $\int{f(x)}+\int{g(x)}+\int{h(x)}$ but $\int{f(x)*g(x)}$ does not equal $\int{f(x)}*\int{g(x)}$

Anyways so $$=2[(-\frac{2}{9}(w)^{9/2}+\frac{6}{7}(w)^{7/2}-\frac{6}{5}(w)^{5/2}+\frac{2}{3}(w)^{3/2})]^0_1$$


  • $\begingroup$ edited, please explain "you can't antidifferentiate an integrand factor by factor." In a way I can understand (understood) :p... Thanks for all the help by the way $\endgroup$ – helpmeh Jan 12 '16 at 20:05
  • $\begingroup$ Given two functions $f(x)$ and $g(x)$, for which you know the antiderivatives $\int f(x)\ dx = h(x)$ and $\int g(x)\ dx = i(x)$, you cannot say that $\int f(x)g(x)\ dx = h(x)i(x)$. Integration, sadly, just isn't that simple. That's why in my answer I said you should expand out $(1-w)^3\sqrt{w}$ instead of just evaluating it directly at the stage $\int (1-w)^3\sqrt{w}\ dw$. $\endgroup$ – user137731 Jan 12 '16 at 20:08
  • $\begingroup$ That (your latest edit) doesn't work either. Reread the last paragraph of my answer. $\endgroup$ – user137731 Jan 12 '16 at 20:19
  • $\begingroup$ edited, check it out, or are you saying i should expand $(1-w)^{3}=-w^{3}+3w^{2}-3w+1$ $\endgroup$ – helpmeh Jan 12 '16 at 20:22
  • $\begingroup$ @helpmeh $\int f(x) \cdot g(x) dx \neq \int f(x) dx \cdot \int g(x) dx$ This is what bye is saying above. $\endgroup$ – randomgirl Jan 12 '16 at 20:25

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.